Synthetic Study of Matrine-Type Alkaloids: Stereoselective Construction of the AB Rings of the Quinolizidine Skeleton - Tsukano, Chihiro; Oimura, Atsuko; Enkhtaivan, Iderbat; Takemoto, Yoshiji (Synlett, 2014)
A new method has been developed for the stereoselective construction of the AB rings of the quinolizidine skeleton of matrine-type alkaloids with a cis-cis stereochemistry. The key features of this method involve: (i) construction of the quinolizidine by reduction of an acylpyridinium cation; and (ii) late-stage introduction of methoxypyridine by sequential Stille coupling and diastereoselective hydrogenation reactions.
Keywords: quinolizidines; stereoselective synthesis; alkaloids; matrine; pyridines